System Administration Order Apparel Children In CV. Jernih Garment Using Access 2000 - Afriandany Xaverius (Jurnal Sistem Informasi, 2006)
Computerization holds a very important role in determining the performance and progress or not a company, it is because the speed, accuracy and completeness or accuracy of the data processing process in which there calculations and data storage is very good. The benefits of computerization can be felt not only by large companies but also by medium and small companies (individuals), one computer advances can also be seen from the processing system database known as the "Database", which is where certain data is collected and classified into their respective groups until finally the data are stored, making it easier for the parties such as cashier, operators, managers to seek and obtain such data with ease. Finally it can be concluded that based on computerized data processing is helping a company, then the author wants to discuss this about computerization that can be associated with the administration system on a CV. Jernih Garment.